A new genus of Drepanicinae (Neuroptera: Mantispidae) from the earliest Eocene Fur Formation, Denmark - Makarkin, Vladimir N.; Perkovsky, Evgeny E.; Nielsen, Christian (Zootaxa, 2025)
Danomantispa frandseni gen. et sp. nov. (Neuroptera: Mantispidae: Drepanicinae) is described from the earliest Eocene Fur Formation, Denmark. This is the first record of Mantispidae from this formation, and the northernmost finding of Drepanicinae. The new genus is easily distinguished from other drepanicine genera by mantispine-like pterostigma: the distal crossvein between Sc and RA is located in the distal part of the pterostigma, and the section of Sc distad it is nearly straight and rather short. Both Cenozoic genera (this genus and Vectispa Lambkin, 1986) are to some degree intermediate between Drepanicinae and Mantispinae: Danomantispa gen. nov. is a drepanicine with a mantispine-like pterostigma, and Vectispa is most probably a mantispine with a drepanicine-like pterostigma. Data on the climatic conditions of the existence of the subfamily in the past and today are summarized. We assume that the Fur Formation climate at the time of D. frandseni sp. nov. was highest microthermal/low mesothermal.